L162v Polymorphism of Par-Α Gene, A603g Polymorphism of Tissue Factor Gene and Risk of Coronary Heart Disease in Russian Population - E.G., Sergeeva; O.A., Berkovich; Z.I., Ionova; M.I., Zaraisky; E.I, Baranova (Journal of Bioinformatics And Diabetes, 2019)
Purpose The goal of this study is to determine the association of L162V polymorphism of PPAR-alpha gene, A603G polymorphism of tissue factor gene and the risk of coronary heart disease development in Russian population.   Materials and Methods A clinical and genetic study of 414 patients with CHD and 220 people of comparable age without CHD which amounted to a control group was performed. L162L and L162V genotypes of L162V polymorphism of PPAR-α gene, A603A, A603G and G603G genotypes of A603G polymorphism of tissue factor gene were determined by polymerase chain reaction followed by restriction analysis. Results A carriage of L162V genotype and V allele of PPAR-α gene was associated with an increase risk of CHD in 2,13 times (L162V genotype) and in 2,21 times (V allele), with an increase in risk of CHD before the age of 45 years in 4,68 times (L162V genotype) and in 3,88 times (V allele). Significantly higher in patients with CHD compared with the general population and in patients with a carriage of G603G genotype and G allele of tissue factor gene was associated with the increase of CHD risk in 2,68 times (G603G genotype) and in 4,37 times (G allele), occurred more frequently in patients with debut of disease at age of 45 years and younger. The level of tissue factor was significantly higher in patients with CHD – carriers G603G genotype compared with carriers A603A genotype (217,9±15,2 pg/ml and 152,6±30,4 pg/ml, respectively, p=0,04). A carriage of the combination of L162V and G603G genotypes was associated with an increased risk of CHD in 3,04 times. Conclusion A carriage of V allele of L162V polymorphism of PPAR-α gene and G allele of A603G polymorphism of tissue factor gene, as well as their pair combination are associated with an increased CHD risk, especially at age 45 years or less.
Keywords: peroxisome proliferator-activated receptor; PPAR; A603G polymorphism; tissue factor; L162V polymorphism; coronary heart disease.